Construction of microneedle of Atractylodes macrocephala Rhizoma aqueous extract and effect on mammary gland hyperplasia based on intestinal flora - Ping, Yang; Gao, Qi; Li, Changxu; Wang, Yan; Wang, Yuliang; Li, Shuo; Qiu, Mingjing; Zhang, Linqian; Tu, Ailing; Tian, Yu; Zhao, Hong (Frontiers in Endocrinology, 2023)
Background A microneedle patch loaded with Atractylodes macrocephala Rhizoma water extract was prepared for the treatment of mammary gland hyperplasia. To explore the relationship between Mammary gland hyperplasia and intestinal flora. Materials and methods Preparation of the microneedle patch by micromolding method, the prescription of the microneedle was optimized by the Box-Behnken Design response surface test, and the micro-morphology, penetration, toughness, and brittleness were investigated. In vitro release of drug-loaded microneedles was measured by diffusion cell method. The rat model of mammary gland hyperplasia was prepared by the combination of estradiol benzoate-progesterone, and the microneedle patch of Atractylodes macrocephala Rhizoma aqueous extract was used for intervention treatment. The change of levels in E2, P, and PRL in rat serum was determined. The intestinal contents of rats were collected and the changes in intestinal flora in MGH rats were analyzed by 16s rRNA high-throughput sequencing. Results The optimized microneedle formula is a PVA concentration of 6.0%, HA concentration of 15.5%, and PVPK30 concentration of 16.0%. The prepared microneedle tip loaded with Atractylodes macrocephala Rhizoma aqueous extract has complete, sharp, and no bubbles and the needle rate of the microneedle array is in the range of 95%~100%. The bending rate of the microneedle is about 12.7%, and it has good flexibility, and the microneedle can puncture 4 layers of ParafilmⓇ membrane smoothly, and the puncture rate is more than 96%. The in vitro release of the microneedle was characterized by rapid release. The results of animal experiments showed that Atractylodes macrocephala Rhizoma aqueous extract microneedle patch could significantly reduce the E2 level, significantly reduce the PRL level, and significantly increase the P level. At the same time, it can regulate the abundance and diversity of intestinal flora in MGH rats, improve the intestinal flora disorder caused by mammary gland hyperplasia, and balance the community structure. Conclusion The prepared microneedle containing Atractylodes macrocephala Rhizoma aqueous extract has good toughness and brittle strength, can penetrate the skin and enter the dermis, and effectively deliver drugs to play a role in the treatment of mammary gland hyperplasia.